2021
DOI: 10.3390/ijms221910187
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Isothiocyanates, Sulforaphane and 2-Phenethyl Isothiocyanate, Effectively Impair Vibrio cholerae Virulence

Abstract: Vibrio cholerae represents a constant threat to public health, causing widespread infections, especially in developing countries with a significant number of fatalities and serious complications every year. The standard treatment by oral rehydration does not eliminate the source of infection, while increasing antibiotic resistance among pathogenic V. cholerae strains makes the therapy difficult. Thus, we assessed the antibacterial potential of plant-derived phytoncides, isothiocyanates (ITC), against V. choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The MIC of AITC for all tested bacteria was 100 μg/mL [ 58 ]. The MIC of phenethyl isothiocyanate (PEITC), which is also prevalent in cruciferous plants, ranges from 41 to 81 μg/mL [ 15 ]. Flavonic acid BB, derived from plants, inhibits clinical S. haemolyticus strains and their biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIC of AITC for all tested bacteria was 100 μg/mL [ 58 ]. The MIC of phenethyl isothiocyanate (PEITC), which is also prevalent in cruciferous plants, ranges from 41 to 81 μg/mL [ 15 ]. Flavonic acid BB, derived from plants, inhibits clinical S. haemolyticus strains and their biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SFN inhibits S. dysenteriae by negatively regulating the expression of Shiga toxin [ 12 ]. SFN and related compounds exhibit a strong inhibitory effect on H. pylori , a bacterium responsible for human gastritis and stomach cancer, and effectively impair the virulence of V. cholerae [ 13 , 14 , 15 ]. Available evidence in the model plant A. thaliana suggested that SFN also has antimicrobial potential against plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The SFN action in promoting phagocytosis was widely investigated previously [43,44]. In our recent work, we have shown that this mechanism is involved in bacterial clearance in the V. cholerae infection [23]. The finding of therapeutic properties of SFN in the course of the S. dysenteriae infection of both cell lines and the animal model is a key step in developing the strategy to use the dietary phytoncides in therapy.…”
Section: Sfn Reduces the Toxicity Of S Dysenteriae In Vivomentioning
confidence: 92%
“…Nevertheless, we showed that ITC could inhibit the growth of several bacterial pathogens, including Klebsiella pneumoniae and Staphylococcus aureus. Recently, we also presented evidence for the antibacterial action of ITCs against another toxin-producing bacterium, Vibrio cholerae [23].…”
Section: Introductionmentioning
confidence: 97%